Institution and public healthcare facility cleanness in Nigeria: a principalagent approach - Omobowale, A.O.; Nguezet, P.; Amao, I. (2013)
There are several reasons (Clinically and public health wise) to believe that the level of cleanliness adequately reflect the performance of service delivery actually received by the populace. This study extend the work of Das Gupta, et al. on the analysis of health facility cleanliness by using the principal-agent theory and the accountability framework to answering questions as regards whether accountability framework elements such as voice and client power/compact affect positively the healthcare facilities cleanliness in Nigeria. The study made use of the available QSDS data of the World Bank in Nigeria in 2004 and complemented it with Focus Groups Discussion (FGDs). Iinstrumental variable probit model was used for the data analysis. The results show that accountability framework elements do affect positively the health service delivery in Nigeria. Specifically, client power explains the level of cleanliness of health facility in Kogi and Lagos states. In addition, the staff skill is another key factor that drives cleanliness positively in health facility in the two states. Therefore, the key policy issues to be targeted are in the area of promoting positive community participation in health facilities in order to enhance cleanliness in health facilities in Nigeria.